English at San Marcos Undergraduate School - Lozada Trimbath, Minnie Eloisa (2010)
The study focuses on the conception the Academic Professional Schools of San Marcos University and the teachers of foreign languages have of English courses at the undergraduate level. The sources used include documents from the Schools and ideas expressed, through interviews, by the authorities. The influence of globalization in the implementing of English is present for some fields of specialization. The findings of the study show, on the one hand, the usefulness English has for the students in the Schools and, on the other, the relationship between Schools expectations and English teachers' ideas. Something outstanding is the concern Heads of Schools have to help students develop this necessary, ability for a professional of the XXI century: the control of the English language.